TECHNOLOGY LEADERS OF COMPUTER AND WEB 2.0 USAGE IN HIGHER EDUCATION: CASE STUDY - Marošan, Zoran T; Jošanov, Borislav; Savić, Ninoslava (International Journal of Economic Practice and Policy, 2016)
Development of ICT usage and open concepts brought new learning paradigm of knowledge creation to the higher education. Main role in this new concept in infrastructure aspect is reserved for web 2.0. The authors of this paper present the case study with the experience of students in the higher education institution. In the first part of the study authors analyze the data collected from the students related to Internet access and Internet activities from them. This research was conducted using questionnaires based on indicators defined by Eurostat and data authors found in the students’ projects created by web 2.0 tools. The main part and purpose of this paper is to analyze how students in Serbia are using web 2.0 tools in their research work. Authors found trends in web 2.0 tools usage and the most popular technologies, concluding that web 2.0 tools are speeding the process of projects development.